2009
DOI: 10.1007/s00535-009-0046-6
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive laboratory tests proposed for predicting cirrhosis in patients with chronic hepatitis C are also useful in patients with non-alcoholic steatohepatitis

Abstract: Noninvasive laboratory tests designed to predict cirrhosis in patients with HCV are also useful in patients with NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 48 publications
0
26
1
Order By: Relevance
“…The platelet count has been included in many scoring systems for the noninvasive prediction of the severity of hepatic fibrosis in patients with chronic hepatitis C, and we have reported that noninvasive laboratory tests proposed for predicting cirrhosis in patients with chronic hepatitis C were also useful in patients with NASH [32]. In recent years Shah et al [33] reported the utility of a scoring system for NAFLD patients in a multicenter trial.…”
Section: Discussionmentioning
confidence: 98%
“…The platelet count has been included in many scoring systems for the noninvasive prediction of the severity of hepatic fibrosis in patients with chronic hepatitis C, and we have reported that noninvasive laboratory tests proposed for predicting cirrhosis in patients with chronic hepatitis C were also useful in patients with NASH [32]. In recent years Shah et al [33] reported the utility of a scoring system for NAFLD patients in a multicenter trial.…”
Section: Discussionmentioning
confidence: 98%
“…Using this score, Calès et al reported an AUROC of 0.866 for significant fibrosis, 0.861 for severe fibrosis, and 0.842 for cirrhosis in a study of NAFLD subjects [102], although significantly lower values were obtained in other studies [101, 109, 110]. …”
Section: Diagnosis and Evaluation Of Nafldmentioning
confidence: 99%
“…By the time a PN-patient has developed jaundice, there is a high likelihood of irreversible bridging fibrosis on liver biopsy [15]. In the adult population, many noninvasive measures of hepatic fibrosis have been developed for use in patients with known liver disease [16][17][18][19][20][21][22][23][24][25][26][27]. These tests allow progressive monitoring of liver disease with very low patient risk and have been shown to decrease rates of liver biopsies at centers where their use is routine.…”
mentioning
confidence: 98%